Cultura organizacional verde y competitividad en las pyme del sector hotelero de la ciudad de Barranquilla. (2017)
The research aimed to analyze the impact of green organizational culture on the competitiveness of SMEs in the hotel sector in Barranquilla, considering the challenge they face in order to strategically and sustainably incorporate variables and environmental initiatives into their management. It was framed in the positivist or quantitative epistemological approach, correlational scope and non-experimental cross-correlation-causal design. For data collection, the survey was used as a technique through a questionnaire with Likert and nominal scales applied to the managers or managerial positions of small and medium-sized hotel companies, groups according to a simple random sampling. The analysis of the results was performed using numerical techniques and scientifically accepted statistics such as frequency distribution, central tendency measurements, control charts, dispersion measurements and parametric analyzes such as the Pearson coefficient and determination. The results allowed to demonstrate that there are characteristics of a green organizational culture and that the key factors of success are developed by the organizations under study, nevertheless the established correlation between the variables is moderate, presenting a coefficient of determination that explains in 31% the Variations in the key factors of success depending on the behavior of the green organizational culture It is concluded that in the context of small and medium-sized hotel companies the collected empirical evidence does not support in a significant way the theoretical foundations that refer to the influence of the green organizational culture on competitiveness.